EFEITO DA INCORPORAÇÃO DE FÁRMACOS ANTIFÚNGICOS SOBRE A MORFOLOGIA DE SUPERFÍCIE E A LIBERAÇÃO IN VITRO DE MATERIAIS MACIOS TEMPORÁRIOS PARA BASE DE PRÓTESE - Aliaga, Adelaida Sánchez (2014)
Purpose: The purpose of this study was to evaluate the surface morphology and roughness and the in vitro leachability of temporary soft liners modified by the incorporation of antifungals, generally used for the denture stomatitis treatment, in their minimum inhibitory concentrations (MIC) for the biofilm of Candida albicans. Material and methods: The surface analyses of the tissue conditioner Softone (S) and the resilient liner Trusoft (T) modified or not by the addition of nystatin (Ny), miconazole (Mc), ketoconazole (Ke), chlorhexidine diacetate (Chx), and itraconazole (It) were made by using scanning electron microscopy and confocal laser microscopy. In vitro leachability of Ny and Chx was measured using Ultraviolet visible spectroscopy. Additional analyses of the modified materials containing Ny and Chx were made using differential scanning calorimetry (DSC). The antifungals were incorporated at their previously determined MIC for the biofilm of C. albicans (Ny = 0.032 g; Mc = 0.256 g; Ke = 0.128 g; Chx = 0.064 g; and It = 0.256 g/g of material). The specimens were stored in distilled water at 37ºC for up to 14 days previously to the analyses. Results: Softone had more irregular surface morphology than Trusoft did. Morphological changes were noted in both materials with increasing immersion time, particularly in those containing drugs. Ny and Ke showed the smallest particle sizes, while Chx and It showed the largest ones. Groups containing Chx and It presented extremely porous and irregular surface. Modified specimens had superior roughness (Ra) values in comparison with the control specimens. There was a trend towards an increase in Ra parameter after 7 days, followed by a decrease to values lower than the initial ones after 14 days, in the control and specimens with Ny, Mc, and Ke. Both materials had biexponential kinetics of release: a rapid initial release followed by a slower leaching. Softone leached more concentration of the antifungals than Trusoft and chlorhexidine was released at higher concentration than nystatin. DSC analysis revealed low Tg for Softone and that the fusion temperature of the drugs changed little after they had been added to the materials. Conclusion: The addition of Chx or It changed more significantly the surface of the materials. Softone was able to release more drug concentration and it was noted a weak chemical bond between the drugs and the evaluated materials.